Retrospective Analysis of 277 Cases of Placenta Accreta Spectrum Diagnosed with Ultrasound at A Single Tertiary Care Center - Adora, Hadikagusti; Yusrawati, Yusrawati (Andalas Obstetrics And Gynecology Journal, 2023)
Introduction : Placenta accreta spectrum (PAS) is characterized by abnormal placental adherence and failure to separate from the uterine wall after delivery. The PAS-associated morbidities include peripartum hysterectomy (loss of fertility), massive hemorrhage and the requirement of blood transfusion (leading to consumptive coagulopathy and multisystem organ failure), admission to the intensive care unit (ICU), injury to adjacent organs, and death. Its incidence is on the rise due to an increasing number of caesarean deliveries. Objective : The goal of our study is to analyze the characteristics and outcomes of PAS managed at a tertiary care center with a high volume of PAS. Methods : The design of analytic observation research with a retrospective cross sectional method with ultrasound diagnosis of PAS at M. Djamil Central General Hospital from January 2020 to December 2022 was reviewed. Details of obstetric backgrounds, predelivery diagnosis, peripartum management, and outcomes were analyzed with mean difference test and chi square. Results :Â Two hundred and seventy-seven women with PAS were identified with ultrasound from 4,500 deliveries during the study period (6.15%). Approximately 45.48% of women with PAS had hysterectomy, while 54.52% did not; 3 cases were conservatively performed. Emergency and elective caesarean sections were accomplished in 32.85% and 67.15%, respectively. There was 3.25% maternal mortality. Anterior PAS (83.3%) is associated with attachment to the previous uterine scar and intraoperative blood loss compared to posterior PAS (15.88%) (p<0.05). The PAS patients with previous uterine surgery had the highest chance of peripartum hysterectomy (p<0.001). Conclusion : The placenta accreta diagnosed by antepartum ultrasound is approximately 6.15%. Almost half of the women in the study had hysterectomies. Only one-third of women with PAS in our study underwent emergent surgery. Anterior PAS is associated with placental attachment to the previous uterine scar and greater intraoperative blood loss compared with posterior PAS. The history of previous uterine surgery in women with PAS increased the chance of peripartum hysterectomy even further. The placenta accreta spectrum should be managed in a center with a high level of surgical expertise.